2007
DOI: 10.1002/mawe.200700143
|View full text |Cite
|
Sign up to set email alerts
|

Design of wear and corrosion resistant PVD‐coatings for magnesium alloys

Abstract: Although magnesium alloys became popular in the first half of the 20 th century, the bad corrosion properties prevented their breakthrough in industrial mass production. Since the technology for the production of high purity alloys was introduced in the 1970s, magnesium alloys became more and more in the focus of industrial attention. Today magnesium alloys are state of the art in structural parts in automotive industry. Despite its outstanding properties like good castability, low density and nearly unlimited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…As a result, the vapor stream condenses on the substrate surface and loses most of the energy as the heat of condensation, thus providing a thermal load on the substrate. [17][18][19] Figure 2 indicates the temperature rise measured for several specimens coated with different substrate speeds and under different conditions. Such conditions include cases of Al or Al-12.6% Si, either with or without plasma activation.…”
Section: Pvd Coating Processmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, the vapor stream condenses on the substrate surface and loses most of the energy as the heat of condensation, thus providing a thermal load on the substrate. [17][18][19] Figure 2 indicates the temperature rise measured for several specimens coated with different substrate speeds and under different conditions. Such conditions include cases of Al or Al-12.6% Si, either with or without plasma activation.…”
Section: Pvd Coating Processmentioning
confidence: 99%
“…18,20 The bombardment of argon atoms on the substrate resulted in the removal of nanoparticles or fine oxides and was responsible for activating the surface and enhancing adhesion between the substrate and coating. 18,20 In a group of experiments for optimizing the ionetching procedure, the temperature of the substrate was monitored. It was found that during ion-etching, the substrate temperature increased, as shown in Fig.…”
Section: Substrate Surface Pretreatment and Ion Etchingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, magnesium is highly susceptible to corrosion in the electrolytic physiological environment and could loose mechanical integrity before new tissue sufficiently heals which limits its orthopedic application [11,14,18,19]. Many surface coating techniques were developed to mitigate corrosion by separating the metal surface from its surroundings or incorporation of corrosion inhibiting chemicals [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%